Figurka ornitomorficzna z Międzyrzecza w województwie lubuskim - Indycka, Agnieszka (Folia Praehistorica Posnaniensia, 2012)
Rescue excavations undertaken in 2004 in advance of the construction of the first part of the Międzyrzecz ring road, entailed the investigation of a multicultural settlement site Międzyrzecz 10. The site produced a fragmented clay ornithomorphic figurine of a water bird, most probably a duck. The chronology of the figurine was estimated at the final Bronze Age (V BA) – the beginning of the Iron Age (Hallstatt period). Unfortunately, the figurine was a stray find from a secondary deposit. The item – a whole figurine on one limb – belongs to the most frequent group among individual representations of birds. The representation of the bird is one of the most common motifs in the figurative art in the western province of the Lusatian culture towards the end of the Bronze Age and in the Hallstatt period.